THE ROLE OF PANCREATIC ENZYMOTHERAPY IN POSTNATAL ADAPTATION OF THE PREMATURE INFANTS UNDER ARTIFICIAL FEEDING - V.V. Dashichev; N.V. Olendar'; A.A. Andreev; D.V. Asherova ("Paediatrician" Publishers LLC, 2007)
Due to immaturity of the digestive system of the premature children under artificial feeding there may often be effects of gastrointestinal tract dysfunctions, which disturb postnatal adaptation among these newborns. The purpose of this research was to analyze a number of indices, characterizing the dynamics of the body weight and functional status of the gastrointestinal tract among the premature children, who received modern active digestive ferment at different periods of time. The authors presented the findings of the retrospective analysis of the case history among 29 premature children, who were held in the department of the premature children of the perinatal center. Children received pancreatine ferment (Creon 10000, Solvay Pharma, Germany). The ferment was introduced in the dosage of 150mg/day. This dose was orally introduced by minimicrospheres during every feeding and in some cases through the nasogastric probe. The ferment intake started in the early neonatal period among 13 children and in the late neonatal period among 16 children. During the course of the ferment therapy the frequency of the symptoms of the gastrointestinal tract dysfunctions drastically reduced. When the course of the ferment therapy was prescribed at an early age, the body weight increase tended to higher indices among premature children during the first month of their lives. Key words: premature children, pancreatic enzymotherapy, gastrointestinal tract dysfunctions.